Improving Instruction in Universities: A Case Study of the Ontario Universities Program for Instructional Development (OUPID) - Elrick, Mei-Fei (Canadian Journal of Higher Education, 1990)
In the late I960's and 1970's, universities established programs, projects, and offices to improve the quality of undergraduate teaching. One of these, the Ontario Universities Program for Instructional Development (OUPID), was created to develop teaching in Ontario's 16 universities. It employed two methods, individual grants and institutional grants, to fulfill its mandate. The Program's limited impact on teaching was attributed to the amount of money, $2,500,000 earmarked for OUPID during its seven years of operation (1973-80) and to the lack of a plan. When examined closely, these reasons only partially explain OUPID's limited influence on teaching. It is more illuminating to consider the Program in relation to what most academics and universities value. This reveals that OUPID's methods neither reflected the way academics view good teaching and teaching improvement nor the way the universities believe excellence is fostered. These findings suggest that interventions which seek to change university teaching must agree with and then extend academic and university values. This conclusion has implications for the response universities make as they address the recent concern for the quality of undergraduate education.